The Expression of Soluble C-Type Lectin-Like Receptor-2 (sCLEC-2) in Metabolic Syndrome (Medical Forum Monthly, 2022)
Objective: To find out the levels of “soluble C-type lectin-like receptors-2 (sCLEC-2)” in subjects of metabolic syndrome.Study Design: Cross-Sectional StudyPlace and Duration of Study: This study was conducted at the Ziauddin University and Hospital, Karachi from 30th April 2021 to 1st January 2022.Materials and Methods: The study comprised 45 patients fulfilling the criteria of metabolic syndrome (MetS) based on AHA, which includes the following risk factors: diabetes mellitus, hypertension, central obesity or dyslipidemia. A group of 10 healthy individuals was also recruited as a healthy group. The study was approved by the ethics review committee (ERC) reference code: 3440321TKBC. Demographic and anthropometric data were gathered following informed consent. A physical examination was performed. Venous blood (5 ml) was drawn by using an aseptic technique. Serum was obtained and sCLEC2 levels were assessed by ELISA kit (Bioassay Technology Laboratory BT LAB Cat. No. E7510Hu). The mean, standard deviation (SD), median, and interquartile range (IQR) were used to report numerical data, along with the r and p values. P-value < 0.05 was considered as statistically significant.Results: The mean of sCLEC-2 levels among 45 MetS individuals was 371.8 pg/ml ± 320 pg/ml whereas the median was calculated to be 237 pg/ml IQR of 358.6 pg/ml. In healthy subjects, the mean sCLEC-2 level was 90.6 pg/ml (±37.09 pg/ml) and the median was 98.6 pg/ml (IQR 45 pg/ml). The serum sCLEC-2 levels were significantly high in metabolic syndrome than the healthy individual (p value 0.0001).Conclusion: The increased soluble CLEC-2 expression in metabolic syndrome patients as compared to healthy individuals might be linked to platelet activation and development of atherosclerosis in metabolic syndrome.